ANALYSIS OF REASONING MATHEMATICS EDUCATION STUDENTS REVIEWED FROM THE GENDER - Faridatul Masruroh (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2021)
This research aims to know how the reasoning of mathematics education students in terms of gender. This research is exploratory research with a qualitative approach. This research has chosen a qualitative approach because the primary data used were written or spoken in the form of words. The subject of this research is a student of mathematics education. The main instrument is the researchers themselves, while the auxiliary instruments used are a reasoning test, an interview guide, and a recording tool. The results of the analysis and discussion that have been conducted showed that the male students could identify facts or information orally (understand what is known and what is asked in a question), able to correctly relate facts or information with concepts of knowledge (definition or theorem), so they can determine conclusions based on ideas and the relationship correctly. Female students can correctly identify facts or information orally and in writing instruction (understand what is known and what is asked in a question) and are unable to correctly relate facts or information to the concept of knowledge (definition or theorem) conclusions are drawn are wrong.